2016
DOI: 10.1002/ange.201603978
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Nonheme High‐Spin (S=2) versus Intermediate‐Spin (S=1) Iron(IV)–Oxo Complexes in Oxidation Reactions

Abstract: Mononuclear nonheme high-spin (S = 2) iron(IV)oxos pecies have been identified as the key intermediates responsible for the CÀHbond activation of organic substrates in nonheme iron enzymatic reactions.Herein we report that the C À Hb ond activation of hydrocarbons by as ynthetic mononuclear nonheme high-spin (S = 2) iron(IV)-oxo complex occurs through an oxygen non-rebound mechanism, as previously demonstrated in the CÀHb ond activation by nonheme intermediate (S = 1) iron(IV)-oxoc omplexes.W e also report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…On the basis of the above results, we conclude that iron-oxygen intermediate(s) that prefers C=C cis-dihydroxylation to allylic S; bond activation was generated in this catalytic system exhibiting excellent chemoselectivity, which is different from the preference of the allylic C-H bond activation of cycloalkenes by nonheme metal-oxo complexes. 56,57 It is noteworthy that the enantioselective cisdihydroxylation of acrylates catalyzed by 11 delivered most of the corresponding cis-diols with comparable or even higher enantioselectivities than that of the well-established osmium-based SAD (Figure S5), thus demonstrating that our biologically inspired nonheme iron-based catalysis could serves as a complementary approach to the SAD to some extent.…”
Section: Scope Of Alkenesmentioning
confidence: 90%
“…On the basis of the above results, we conclude that iron-oxygen intermediate(s) that prefers C=C cis-dihydroxylation to allylic S; bond activation was generated in this catalytic system exhibiting excellent chemoselectivity, which is different from the preference of the allylic C-H bond activation of cycloalkenes by nonheme metal-oxo complexes. 56,57 It is noteworthy that the enantioselective cisdihydroxylation of acrylates catalyzed by 11 delivered most of the corresponding cis-diols with comparable or even higher enantioselectivities than that of the well-established osmium-based SAD (Figure S5), thus demonstrating that our biologically inspired nonheme iron-based catalysis could serves as a complementary approach to the SAD to some extent.…”
Section: Scope Of Alkenesmentioning
confidence: 90%
“…63,94 It should however be mentioned that the recent study of Bae et al revealed similar reactivity features of S = 1 and S = 2 structurally similar iron(IV)oxo complexes. 95 There is no high versus low spin dilemma for iron(V)oxo complexes derived from TAML activators, which are S = 1/2 species, and their S = 3/2 state is practically unattainable due to a large gap in the lowest energy, doubly occupied d xy and HOMO d xz orbitals of 18 500 cm −1 . 31 Our major inspiration for probing the ability of Fe V O TAMLs to cleave C−H bonds of hydrocarbons stemmed from their high reactivity in the oxidation of thioanisoles and persistent micropollutants of water (see previous sections).…”
Section: Oxidation Of Hydrocarbons: C−h Bond Cleavage Versus Electron...mentioning
confidence: 99%
“…Oxidation of C-H and C=C bonds is a main topic in chemistry and specifically in catalysis research [31]. Even though highvalent iron systems excel at both of these transformations [32,33], non-heme iron(IV)-oxo species generally prefer C-H over the C=C bond oxidation [34,35]. The epoxidation has been achieved by additives such as acids [36], or using iodosylarene-based oxidants, instead of iron-oxo species [37] or using substrates with deuterated C-H bonds [38].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%